Effects of aluminum hydroxide and calcium carbonate antacids on the bioavailability of ciprofloxacin. - Frost, R W (1992)
This study was designed to determine the effects of an aluminum hydroxide antacid and a calcium carbonate antacid on the bioavailability of ciprofloxacin (Cipro). Cipro (750 mg) was administered orally to 12 healthy volunteers in a three-way randomized crossover design. The three treatments included Cipro alone, four 850-mg calcium carbonate tablets taken 5 min before Cipro, and three 600-mg aluminum hydroxide tablets taken 5 min before Cipro. The relative bioavailability of Cipro when given with calcium carbonate was approximately 60% of the control value. When Cipro was given with aluminum hydroxide, the relative bioavailability was approximately 15%. Urinary recovery of Cipro in the aluminum hydroxide treatment group was approximately one-fourth of that in the calcium carbonate group. Although calcium carbonate decreased absorption to a lesser extent than aluminum hydroxide, these data suggest that antacids containing either aluminum or calcium should not be given concomitantly with Cipro.